2019
DOI: 10.1111/srt.12682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human electroencephalogram change for sensory effects of fragrance

Abstract: Background The stabilizing effect of lavender and the arousal effect of peppermint essential oils are acknowledged and used widely in aromatherapy and the cosmetics industry. However, no evaluation method confirms the effects of essential oils through quantitative and objective electroencephalogram (EEG) results; instead, only a psychological and subjective method exists. Therefore, this study aims to create a new emotional cosmetic evaluation paradigm using EEG values. Moreover, it enables quantitative interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Indeed, Saiorwan and colleagues [32] found decrease in autonomic parameters and increase of band power in alpha, beta and theta waves during the lavender inhalation, indicating arousal decrease. These findings are corroborated by one EEG study which reported increased alpha wave after lavender inhalation, suggesting a relaxing effect [48]. Moreover, Diego and colleagues [47] showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks.…”
Section: Lavender Eo and Cognitionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, Saiorwan and colleagues [32] found decrease in autonomic parameters and increase of band power in alpha, beta and theta waves during the lavender inhalation, indicating arousal decrease. These findings are corroborated by one EEG study which reported increased alpha wave after lavender inhalation, suggesting a relaxing effect [48]. Moreover, Diego and colleagues [47] showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks.…”
Section: Lavender Eo and Cognitionmentioning
confidence: 70%
“…Moreover, Diego and colleagues [47] showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks. It is worth noting that Diego and colleagues [47] and Park and colleagues [48] also studied cognitive effects of lavender EO, however these studies were not included in this systematic review because were based on a within-subject design. Moreover, beta power is reported to be also related to less pronounced attentional blink [49] and this supports the hypothesis of a possible causal relation between lavender inhalation, arousal decrease and higher tonic attention performance.…”
Section: Lavender Eo and Cognitionmentioning
confidence: 99%
“…San Diego, CA [22] CGX© GmbH, Gilching, Germany [25] Emotiv© EMOTIV, San Francisco, CA [17,13] EEGLAB SCCN, La Jolla, CA [137] G-Tec© GmbH, Austria [24] mBrainTrain© Beograd, Serbia [16] Muse TM InteraXon Inc., Toronto, ON [1,23] NeuroElectrics TM Cambridge, MA [15] Neuroscan© Compumedics, Victoria, Australia [18] NeuroSky© NeuroSky Inc, San Jose, CA [21] OpenBCI© Brooklyn, NY [27] Open Vibe©…”
Section: Manufacturer Location Citationmentioning
confidence: 99%
“…EEG is a method of measuring the electrical activity of neuron cells and has been shown to be effective at detecting concussion [10,11,12]. There are various tools available for the detection of EEG, ranging from consumer grade to clinical grade, and costing anywhere from hundreds to hundreds of thousands of dollars [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. EEG detection is becoming more available, with more consumer grade devices being made for use at home.…”
mentioning
confidence: 99%
“…Human sensory systems are involved in daily activities, both consciously and unconsciously, and a study of the senses, especially their connection with brain activity, has been gaining in popularity in recent years. Brain activity analysis using electroencephalography (EEG) has received considerable attention [2][3][4][5][6] , particularly in relation to the ve basic human senses: sight 2 , touch 7 , hearing 8,9 , smell [10][11][12][13] and taste 14 . In addition to EEG, a number of optical techniques have also been employed for monitoring human brain activity using image contrast analysis 15,16 and cross-correlation based analysis of a laser speckle imaging 17 .…”
Section: Introductionmentioning
confidence: 99%